2018
DOI: 10.1155/2018/3561962
|View full text |Cite
|
Sign up to set email alerts
|

The Female Athlete’s Heart: Comparison of Cardiac Changes Induced by Different Types of Exercise Training Using 3D Echocardiography

Abstract: We aimed to characterize female athlete's heart in elite competitors in the International Federation of Bodybuilding and Fitness (IFBB) Bikini Fitness category and compare them to athletes of a more dynamic sport discipline and healthy, sedentary volunteers using 3D echocardiography. Fifteen elite female fitness athletes were recruited and compared to 15 elite, age-matched female water polo athletes and 15 age-matched healthy, nontrained controls. Using 3D echocardiography, left ventricular (LV) and right vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The nature of these changes is also influenced by other factors, such as age, gender, ethnicity, type of sport, cumulative years of training, and degree of conditioning. 4,[17][18][19][20] To the best of our knowledge, our study is the first to correlate LA morphology and function assessed by 3D echocardiography with CPET in a relatively large set of elite athletes. The atrial enlargement and low-normal function found in our population do not represent dysfunction but a physiologic aspect of the ''athlete's heart'': less contraction in a higher volume chamber can achieve the same stroke volume as a smaller one with more pronounced shortening.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of these changes is also influenced by other factors, such as age, gender, ethnicity, type of sport, cumulative years of training, and degree of conditioning. 4,[17][18][19][20] To the best of our knowledge, our study is the first to correlate LA morphology and function assessed by 3D echocardiography with CPET in a relatively large set of elite athletes. The atrial enlargement and low-normal function found in our population do not represent dysfunction but a physiologic aspect of the ''athlete's heart'': less contraction in a higher volume chamber can achieve the same stroke volume as a smaller one with more pronounced shortening.…”
Section: Discussionmentioning
confidence: 99%
“…There were a total of 1734 results from the literature search with 22 studies meeting inclusion criteria (D’Ascenzi et al, 2017 ; Doronina et al, 2018 ; Hedman et al, 2015 ; Henriksen et al, 1999 ; Kooreman et al, 2019 ; Kramer et al, 2013 ; Lakatos et al, 2018 ; Leischik & Spelsberg, 2014 ; Leischik et al, 2016 ; Luijkx, Cramer, et al, 2012 ; Luijkx, Velthuis, et al, 2012 ; Malmgren et al, 2015 ; Mangold et al, 2013 ; Petersen et al, 2006 ; Prakken et al, 2010 , 2011 ; Sanz‐de la Garza et al, 2017 ; Steding‐Ehrenborg et al, 2016 ; Stolt et al, 2000 ; Venckunas et al, 2016 ; Zeldis et al, 1978 ). Of the studies that met the inclusion criteria, three were case series (Kooreman et al, 2019 ; Leischik & Spelsberg, 2014 ; Mangold et al, 2013 ), 16 were cross sectional (Doronina et al, 2018 ; Hedman et al, 2015 ; Henriksen et al, 1999 ; Kramer et al, 2013 ; Lakatos et al, 2018 ; Leischik et al, 2016 ; Luijkx, Cramer, et al, 2012 ; Luijkx, Velthuis, et al, 2012 ; Malmgren et al, 2015 ; Petersen et al, 2006 ; Prakken et al, 2010 , 2011 ; Sansonio de Morais et al, 2017 ; Sanz‐de la Garza et al, 2017 ; Stolt et al, 2000 ; Zeldis et al, 1978 ), and three were cohort (with historical control) studies (D’Ascenzi et al, 2017 ; Steding‐Ehrenborg et al, 2016 ; Venckunas et al, 2016 ). A total of 529 HC, 501 EA, 421 MA, and 78 strength athletes (SA) results were inc...…”
Section: Resultsmentioning
confidence: 99%
“…Transthoracic echocardiography assessment of LV size revealed a 17% greater LVEDV (Doronina et al, 2018 ; Kooreman et al, 2019 ; Lakatos et al, 2018 ; Leischik & Spelsberg, 2014 ; Leischik et al, 2016 ; Malmgren et al, 2015 ; Sanz‐de la Garza et al, 2017 ; Zeldis et al, 1978 ) (72.9 vs. 61.0 ml/m 2 ; p < 0.001) and a 27% greater LVESV (Doronina et al, 2018 ; Lakatos et al, 2018 ; Leischik & Spelsberg, 2014 ; Leischik et al, 2016 ; Malmgren et al, 2015 ) in EA versus HC (30.3 vs. 22.1 ml/m 2 ; p < 0.001). LVEF (Doronina et al, 2018 ; Hedman et al, 2015 ; Kooreman et al, 2019 ; Lakatos et al, 2018 ; Leischik & Spelsberg, 2014 ; Leischik et al, 2016 ; Malmgren et al, 2015 ; Venckunas et al, 2016 ) tended to be lower by 3% in EA versus HC (59.9% vs. 61.9%; p = 0.21). Assessment of RV function revealed a 28% greater RVEDV (Doronina et al, 2018 ; Lakatos et al, 2018 ) (83.5 vs. 59.6 ml/m 2 ; p < 0.001) and a 37% greater RVESV (Doronina et al, 2018 ; Lakatos et al, 2018 ) in EA versus HC (37.1 vs. 23.0 ml/m 2 ; p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Water polo players are susceptible to hemodynamic changes and remodeling of cardiac chambers, as an adaptive mechanism to the long-standing exposure to intense, mixed endurance and strength training. It has been shown that increased demands for oxygen consumption and tissue perfusion in those subjects result in increased left ventricle thickness, end-diastolic volume, and cardiac output [11, 18]. Concerning the arterial function and arterial wall properties in elite athletes, there is evidence supporting increased arterial diameter and decreased wall thickness [19].…”
Section: Discussionmentioning
confidence: 99%